Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have been trying to figure out how the following has been simplified, but I am getting nowhere with it. Anyone have any ideas?

$9(n/3)^{5/2}$ to $(1/3)^{1/2} f(n)$

It is given that $f(n) = n^{2.5}$.

share|improve this question
1  
Neither algorithms nor computer-science seem like appropriate tags. –  mrf Jan 9 '13 at 23:41
add comment

2 Answers

up vote 4 down vote accepted

$$\begin{align*} 9\left(\frac{n}3\right)^{5/2}&=9\left(\frac13\right)^{5/2}n^{5/2}\\\\ &=3^2\cdot 3^{-5/2}f(n)\\\\ &=3^{2-5/2}f(n)\\\\ &=3^{-1/2}f(n)\\\\ &=\left(\frac13\right)^{1/2}f(n) \end{align*}$$

share|improve this answer
add comment

$$9\left(\frac{n}{3}\right)^{5/2} = 9\cdot \left(\frac13\right)^{5/2} n^{5/2}$$ $$=9\cdot\dfrac{1}{3^{5/2}} f(n)$$ $$= \dfrac{3^2}{3^2\cdot3^{1/2}}f(n)$$ $$= \frac{1}{3^{1/2}}f(n)$$ $$=\left(\dfrac{1}{3}\right)^{1/2} f(n)$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.